Technologies as Resources for Inclusive Education: Subtitled Videos for Hearing Impaired Students Learning - Monar Ibarra, Kevin Josué (2023)
The purpose of this work is to present the use of technologies to support students with hearing disabilities in a Higher Education center in Ecuador. Specifically, the perception of students in relation to the use of video with subtitles for their training, content comprehension and learning is analyzed. The research methodology implemented has been the construction of a mixed methodological design of a descriptive nature. For this, a 22-item questionnaire was elaborated combining the Likert scale with open and close-ended questions. The instrument was applied to a sample of 40 students from the Superior Technology in Administration in a college in Guayaquil. The results revealed the positive perception of students with hearing disabilities regarding the use of video with subtitles and report on the better understanding of theoretical content with the use of this technological tool in students with and without hearing disabilities. Also, there is a greater motivation in the teaching and learning process with the use of this resource among students with hearing disabilities. These results allow us to confirm the benefits of video subtitling, which in turn should encourage high education teachers to implement it in learning environments.